Frequency of Resistance to Third Generation Cephalosporin in Neonates with Septicemia at a Tertiary Care Hospital - Nanga Ram, Ali Akhtar, Nayab Hyder, Fayaz Ali, Shabina Ariff Ahmed, Sajid Bashir Soofi (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Objective: Sepsis in newborns is a serious medical issue everywhere [1]. With an incidence of 1 to 10 per 1000 live births worldwide, newborns are more susceptible to developing bacterial sepsis [2]. With a sepsis-related mortality rate of up to 50% for untreated neonates, the problem of sepsis is significantly more prevalent in poor nations than in industrialised ones. Neonatal sepsis is a clinical illness that affects infants younger than 28 days of age and is characterised by a variety of generalised, non-specific systemic symptoms [3]. Therefore, this study was conducted to determine the frequency of resistance to 3rd generation cephalosporin in neonates with septicemia at a tertiary care hospital. Materials and Methods: A cross-sectional study was conducted at the NICU of the Aga Khan University Hospital Karachi and nursery departments of the four affiliated secondary care Hospitals from December 2020 to December 2021. We included 477 neonates with sepsis aged 0 to 28 days of life using the non-probability consecutive sampling method. Data were analysed in SPSS version 23.0. All categorical variables were presented as frequencies with percentages, and continuous variables (were presented as mean ±SE. Poststratification applies in gchi-squaretest taken p-value less than equal to 0.05 taken as significant. Results: A total of 377 patients were enrolled. Majority of the patients were preterm neonates, and 70% of the bacterial isolates were resistant to cefotaxime or ceftazidime. 36(9.5%) neonates had bradycardia, 301(79.8%) of neonates had tachycardia, 294 (78%) of neonates had tachypnea, 153 (40.6%) of neonatal sepsis suffered from hypothermia, and 121 (32.1%) of neonatal sepsis patients had a depressed TLC count. Conclusions: We conclude that frequent use of cephalosporin antibiotics has evolved into a high resistance burden. We need local guidelines for the empiric use of antibiotics to cut down the use of cephalosporin, infection control policies to break the chain of infection transmission. Keywords: Neonatal Sepsis, Early-Onset Sepsis, Blood Culture. Cephalosporin Resistance,